(untitled) (Eurasian Journal of Engineering and Technology, 2022)
Safety is very paramount in any industry, especially with manufacturing, forging industries and many others .Therefore we intend to aid these problems in industries by developing a safety parameters monitoring and controlling system, and making it more capable and user friendly by inclusion of IoT. We believe that a system should be well automated so that a new user or a new employee who has no prior experience in controlling a unit should be able to get acquainted very easily. With the help of IoT, administrators will come to know the live status of a unit on which a parameters monitoring and controlling system is installed, it can be done via mails, or if a person is present there they can observe themselves. For example we can set temperature to a certain limit and if temperature exceeds beyond the set limit, the fans or other cooling system will start automatically. This system will also have gas sensors, flame sensors as well as radiation sensors. We are using Arduino UNO ATmega 328 as a controller for this system. Lastly the administrator will have records or logs of the parameters fluctuation and other activities at a particular time so it will be ready for reference in future and this will help the administrator to take security measures.